This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: CS103 HO#31 SlidesInduction III April 28, 2010 1 Complete Induction WellOrdering Principle Mathematical Induction MI CI P 1 P 2 __ __ __ . . . __ __ P k P k+1 Suppose the sequence of propositions P n satisfies the conditions for Complete Induction: We want to show nP n MI CI P 1 P 2 __ __ __ . . . __ __ P k P k+1 Suppose the sequence of propositions P n satisfies the conditions for Complete Induction: Let Q n = P 1 P 2 P 3 P n Q 1 is true since we are assuming that P 1 is true Suppose Q k is true. Then P k+1 is true by the diagram above. Q k P k+1 = Q k+1 , so Q k Q k+1 So by MI, we have nQ n But Q n P n , so we have nP n So MI CI Complete Induction WellOrdering Principle Mathematical Induction Specifying a Sequence Enumerate: 2, 4, 6, 8, ... Explicit formula: a n = 2n, n = 1, 2, ... Recursive formula: a 1 = 2, a n = a n1 + 2 Recursive Definition of a Sequence 1, 3, 6, 10, 15, 21, ... a 1 a 2 a 3 a 4 a 5 a 6 a 1 = 1 a n = a n1 + n Solving the recurrence relation to obtain an explicit formula can be difficult, but here, we can see that a n is the sum of the 1 st n integers, so which we proved by induction. a n = n(n + 1) 2 CS103 HO#31 SlidesInduction III April 28, 2010 2 Recursive Definition of Factorial n!=1 2 3 ... n can be defined recursively: n! = 1 if n = 1 n(n1)! if n > 1 Fibonacci Sequence i f n = 1 i f n = 1 F n1 + F n2 if n > 1 F n = 0, 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, 610, 987 The Explicit Formula (1 + 5) n (1  5) n 2 n 5 F n = 0 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 0, 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, 610, 987 Fibonacci Sequence i f n = 1 i f n = 1 F n1 + F n2 if n > 1 F n = Prove P n : F i = F n F n+1 for n 1 i=1 n 2 0+1+1+4+9+25 = 40 5 8 = 40 0 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 0, 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, 377, 610, 987 Fibonacci Sequence i f n = 1 i f n = 1 F n1 + F n2 if n > 1 F n = Prove P n : F i = F n F n+1 for n 1 i=1 n 2 BASE CASE: P 1 asserts that 1 2 = 1 1, which is true. Fibonacci Sequence i f n = 1 i f n = 1 F n1 + F n2 if n > 1 F n = Prove P n : F i = F n F n+1 for n 1 i=1 n 2 INDUCTIVE STEP: Assume P k : F i = F k F k+1 for some k 1 Show P k+1 : F i = F k+1 F k+2 i=1 k 2 2 i=1 k+1 Fibonacci Sequence i f n = 1 i f n = 1 F n1 + F n2 if n > 1 F n = Prove P n : F i = F n F n+1 for n 1 i=1 n 2 INDUCTIVE STEP: 2 Assume P k : F i = F k F k+1 for some k 1 Show P k+1 : F i = F k+1 F k+2 F i + F k+1 = F k F k+1 + F k+1 by Inductive Hypothesis and adding to both sides F i = F k+1 (F k + F k+1 ) def. of and factoring RHS i=1 k 2 2 i=1 k+1 i=1 k 2 2 2 k+1 i=1 CS103 HO#31 SlidesInduction III April 28, 2010 3 Fibonacci Sequence i f n = 1 i f n = 1 F n1 + F n2 if n > 1 F n = Prove P n : F i = F n F n+1 for n 1 i=1 n 2 INDUCTIVE STEP: 2 Assume P k :...
View
Full
Document
This document was uploaded on 02/08/2011.
 Fall '09

Click to edit the document details